Farmers' crop varieties and farmers' rights: challenges in taxonomy and law - Halewood, Michael (Routledge, 2016)
Farmers play an important role in the development and conservation of crop genetic diversity, and the contribution of that diversity to agro-ecosystem resilience and food security. This book examines policies that aim to increase the share of benefits that farmers receive when others use the crop varieties that they have developed and managed, i.e., ‘farmers varieties’.